The effect of motor imagery and action observation in the rehabilitation of lower limb injuries: A scoping review - Nanbancha A. (2023)
Objective: To synthesize research literature, which has investigated the application of motor imagery and action observation in rehabilitation protocols. Specifically, we aimed to review the implementation of motor imagery and action observation in the rehabilitation of lower limb injuries. Methods: This scoping review followed Arksey and O’Malley's framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension guidelines for scoping reviews checklist. The Medline (PubMed), Cochrane Library, Scopus, and Web of Science databases were searched for controlled clinical trials published between 2010 and 2021 using key search terms. Primary articles were screened for inclusion based upon applying motor imagery and action observation as a rehabilitation protocol (independently or in combination) after sustaining an injury or undergoing surgery. Data were charted by extracting the exercise duration, frequency, and the number of weeks from the rehabilitative intervention protocols, and the measured clinical outcomes (pain, range of motion, muscle activity, and functional outcomes). Results: The initial database search resulted in 1367 articles, with 1352 excluded after screening, resulting in a total of 15 articles eligible for inclusion in the review. Six of the included articles included an action observation intervention, eight studies a motor imagery intervention, and a single study included combined motor imagery and action observation approach. The motor imagery and action observation techniques were able to improve clinical outcomes, including daily activity, functional movement, rage of motion, pain, and muscle strength. Conclusion: Motor imagery and action observation interventions may be effective to improve rehabilitative outcomes of lower limb injuries, thus its application should be considered alongside standard treatment protocols.